Serotonin transporter gene polymorphism (5-HTTLPR) L allele interacts with stress to increase anxiety symptoms in Chinese adolescents: a multiwave longitudinal study - Ming, Qingsen (BMC Psychiatry, 2015)
BACKGROUND: Previous studies of the interaction between a functional polymorphism in the serotonin transporter gene-linked promoter region (5-HTTLPR) and stress in anxiety-related phenotypes have produced inconsistent results. The aim of the current study was to examine the effect of the 5-HTTLPR × stress interaction on anxiety symptoms in Chinese adolescents. METHODS: A total of 651 healthy adolescents [323 females and 328 males; age 14–17 (mean = 16.27, standard deviation = 0.77)] participated in this study. At the initial assessment, participants completed self-report measures assessing anxiety symptoms, depressive symptoms and stressful life events. Additionally, anxiety symptoms and stressful life events were assessed once every 3 months for the subsequent 9 months. A hierarchical linear model (HLM) was used to investigate the 5-HTTLPR × stress interaction. RESULTS: The HLM indicated no main effect of 5-HTTLPR on anxiety symptoms. Significant 5-HTTLPR × stress interaction effect in predicting anxiety symptoms was found. Specifically, individuals with the 5-HTTLPR L allele exhibited more anxiety symptoms related to stressful life events. CONCLUSIONS: The association between stress and anxiety symptoms is moderated by 5-HTTLPR. The 5-HTTLPR L allele increases individuals’ vulnerability to anxiety under stress situations.